2020
DOI: 10.3389/fpsyg.2020.527886
|View full text |Cite
|
Sign up to set email alerts
|

Framing Effects on Online Security Behavior

Abstract: We conducted an incentivized lab experiment examining the effect of gain vs. lossframed warning messages on online security behavior. We measured the probability of suffering a cyberattack during the experiment as the result of five specific security behaviors: choosing a safe connection, providing minimum information during the sign-up process, choosing a strong password, choosing a trusted vendor, and loggingout. A loss-framed message led to more secure behavior during the experiment. The experiment also mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Those with a high-income background, with or without a college degree, have the highest probability of adopting 2FA. This finding is consistent with the notion of loss aversion, that motivates individuals to exhibit behaviors to prevent such losses [25] including in the cybersecurity context [26,27]. In this respect, the higher the income, the more likely people will adopt 2FA despite all the inconvenience that comes with it.…”
Section: Discussionsupporting
confidence: 86%
“…Those with a high-income background, with or without a college degree, have the highest probability of adopting 2FA. This finding is consistent with the notion of loss aversion, that motivates individuals to exhibit behaviors to prevent such losses [25] including in the cybersecurity context [26,27]. In this respect, the higher the income, the more likely people will adopt 2FA despite all the inconvenience that comes with it.…”
Section: Discussionsupporting
confidence: 86%
“…In the cybersecurity context, Anderson and Agarwal (2010) found that users exhibit greater risk-averse behavior when presented with Impact of digital nudging in cybersecurity messages that focus on the benefits of following recommended secure online behaviors than the negative consequences of not following them. In contrast, an experimental study by Rodriguez-Priego et al (2020) found that negative (loss) framing of security risks is more effective in influencing users toward taking more secure behavior than its positive (gain) framing counterpart. Another experimental study by Rosoff et al (2013) did not find any difference in positive versus negative (gain-loss) framing of information security messages.…”
Section: Framing and Priming In Cybersecuritymentioning
confidence: 83%
“…Researchers have utilized prospect theory to evaluate the impact of positively versus negatively framed messages on user behavior (e.g. Aaker and Lee, 2001;Anderson and Agarwal, 2010;Pechmann et al, 2003;Rodriguez-Priego et al, 2020;Rosoff et al, 2013;Sharma, 2017;Shiv et al, 2004;Zhan et al, 2020). In the cybersecurity context, Anderson and Agarwal (2010) found that users exhibit greater risk-averse behavior when presented with Impact of digital nudging in cybersecurity messages that focus on the benefits of following recommended secure online behaviors than the negative consequences of not following them.…”
Section: Framing and Priming In Cybersecuritymentioning
confidence: 99%
“…Framing effect/cognitive bias [66] The phenomena of reflecting cognitive biases, i.e., expressing opinions and decision-making, are influenced by the way a question is asked. This cognitive bias based on language-framing leads to decision manipulation.…”
Section: Sub-domains Of Language/reasoning Descriptionmentioning
confidence: 99%